Identification and potential application of RAPD markers for anthracnose resistance in water yam (Dioscorea alata) - Mignouna, Hodeba D.; Abang, Mathew M.; Onasanya, A.; Agindotan, A.; Asiedu, Robert (2002)
Anthracnose, caused by Colletotrichum gloeosporioides, is the most severe foliar disease of water yam (Dioscorea alata) worldwide. The tetraploid breeding line, TDa 95/00328, is a source of dominant genetic resistance to the moderately virulent fast growing salmon (FGS) strain of C. gloeosporioides.Bulked segregant analysis was used to search for random amplified polymorphic DNA (RAPD) markers linked to anthracnose resistance in F1 progeny derived from a cross between TDa 95/00328 and the susceptible male parent, TDa 95-310. Two hundred and eighty decamer primers were screened using bulks obtained from pooled DNA of individuals comprising each extreme of the disease phenotype distribution. A single locus that contributes to anthracnose resistance in TDa 95/00328 was identified and tentatively named Dcg-1. We found two RAPD markers closely linked in coupling phase with Dcg-1, named OPI71700 and OPE6950, both of which were mapped on the same linkage group. OPI71700 appeared tightly linked to the Dcg-1 locus; it was present in all the 58 resistant F1 individuals and absent in all but one of the 13 susceptible genotypes (genetic distance of 2.3 cM). OPE6950 was present in 56 of the 58 resistant progeny and only one susceptible F1 plant showed this marker (6.8 cM). Both